Catalytic conversion of CO2 to biofuel (methanol) and downstream separation in membrane-integrated photoreactor system under suitable conditions. (1st January 2020) - Chakrabortty, Sankha; Nayak, Jayato; Pal, Parimal; Kumar, Ramesh; Banerjee, Shirsendu; Mondal, Preetam Kumar; Pal, Madhubanti; Ruj, Biswajit
Abstract: A heterogeneous photocatalyst has been developed using sono-chemical assisted sol-gel method by maintaining aweight ratio of 1:2:3 for hydrogen exfoliation graphene, titanium oxide andcopper sulphateand exhaustively characterized. Rigorous experimentations have been done using newly developed heterogeneous photocatalyst for efficient capturing and maximum conversion of carbon di oxide to methanol by mutual effects of governing conditions, like as catalyst dose, pH, CO2 flow rate and temperature. Optimization study has been carried out employing a statistical approach of response surface methodology which reveals the maximum methanol productivity and yield. Approximately, 134 g/Lh of productivity and 40 mg/gcat of yield were found after 3 h of illumination under UV in an annular type Pyrex reactor at an optimum catalyst dosage of 10 g/L, CO2 flow rate of 3 L/m, pH of 3, and process temperature of 50 °C. By the judicial integration of flat-sheet cross flow microfiltration membrane module for catalyst separation and recycle, a steady state permeate flux 145 L/m 2 h was achieved at an applied pressure of 3 bar and cross-flow feed rate of 700 L/h. Graphical abstract: Image 1 Highlights: A membrane integrated system developed for synthesis and purification of methanol. High grade photocatalyst has been synthesized for high yield methanol production. Response surface optimized condition produced the highest concentration of methanol. The system is characterized by high yield, productivity and low price of methanol.